Applying Minderop’s Fictional Characterization to Imaginary Friends in the IF (2024) Movie - Fitri, Farhadia Syawala; Mujani, Sahril; Mashuri, mashuri (STIBA IEC JAKARTA, 2025)
Imagination plays a crucial role in childhood development, often represented through imaginary friends as emotional and cognitive companions. The movie IF (2024) presents a unique narrative that visualizes children’s imaginary friends and their deeper meanings. This research aims to analyze the characterization of imaginary friends. Using a descriptive qualitative approach, this research applies Albertine Minderop’s fictional characterization theory to examine how each imaginary friend is portrayed through name and dialogue. Data is collected through observation of the movie's scenes, character interactions, and dialogues. The findings reveal that imaginary friends are not merely fictional entities but serve as emotional representation of unspoken feelings such as grief, loneliness, and inner strength. This research concludes that IF (2024) offers a profound representation of how imaginary friends can accompany a child's psychological journey, bridging creativity, emotional growth, and the struggle of letting go.